Bisphenol A exposure through receipt handling and its association with insulin resistance among female cashiers. (August 2018) - Lee, Inae; Kim, Sunmi; Kim, Ki-Tae; Kim, Sungkyoon; Park, Suhyun; Lee, Hyojin; Jeong, Yunsun; Lim, Jae-Eun; Moon, Hyo-Bang; Choi, Kyungho
Abstract: Bisphenol A (BPA) is one of the most widely used chemicals in various consumer products. In thermal papers such as receipts and tickets, BPA is used as a heat-activated developer. Cashiers are therefore suspected to be a vulnerable group of exposure to BPA, but neither contribution of receipt handling to the total body burden of BPA among cashiers, nor related health effects are well characterized. Female cashiers (n = 54) were recruited from seven retail shops of a major supermarket chain in Korea, and urinary levels of BPA and metabolic syndrome (MetS) related biomarkers were measured. In order to estimate the contribution of receipt handling to the body burden of BPA, an intervention was designed on the use of gloves: the subjects were asked not to wear gloves during the work for one week, and in the following week, to wear gloves. Urine samples were collected at pre-shift and post-shift for the first two consecutive days in each week, and urinary BPA concentrations were measured. In cashiers without gloves, about a two-fold increase in urinary BPA concentrations was observed after work-shift. When the cashiers wore gloves, however, urinary BPA levels showed no changes. Higher urinary BPA concentrations were associated with greater levels of fasting insulin and insulin resistance. Our observation shows that receipt handling among the cashiers could double the BPA exposure levels at post-shift compared to those at pre-shift, and use of simple protective equipment such as gloves could effectively reduce the BPA exposure levels. Highlights: Contribution of receipt handling to body burden of BPA was determined in cashiers. Without gloves, urinary BPA levels increased by two folds following work-shift. Use of gloves could efficiently prevent occupational exposure to BPA. Urinary BPA levels were associated with increased insulin levels and resistance.